Regional Romanticism - McKeever, Gerard Lee. author. (orcid)0000-0002-2019-3984 Link aut Link
XVI, 304 p. 17 illus., 13 illus. in color.
Keywords: “Regional Romanticism offers a fascinating look at the emergence of regional literature as a category of Romantic expression. McKeever maps out a dialectic between the local and the global that is recorded with increasing complexity in the literary archive. The result is a fine tribute to the ‘debatable lands’ of Dumfriesshire and Galloway that moves well beyond a celebration of the local as such towards a rigorous reflection on book and media history, narrative and lyric form, and the invention of regionalism at a critical historical juncture.” —Eric Gidal, Professor of English, University of Iowa, USA “McKeever’s book offers a paradigm of how to conceive of ‘Regional Romanticism’, as well as an exemplary period-based study of Dumfries and Galloway, that ‘stubbornly in-between place’. Ranging confidently across Romantic genres, it charts the profound implication of the idea of place in an era of global transformation. Bristling with ideas, it will speak to a wide community of readers both within and well beyond the study of Scottish Romanticism.” —Nigel Leask, Regius Chair of English Language and Literature, University of Glasgow, UK This book tracks the rise of modern cultural regionalism across the turn of the nineteenth century. Attending specifically to literature and literary culture, it examines how a particular region—southwest Scotland—was reimagined between 1770 and 1830. Regionalisms were a vital, emergent force in this period, in dialogue with the local, the national, the transnational and the imperial. For southwest Scotland, this process involved visitors like Dorothy Wordsworth and John Keats; resident icon Robert Burns; homesick emigrants such as Allan Cunningham; and the unprecedented success of Walter Scott. Regional Romanticism illuminates a neglected aspect of anglophone literary history, acknowledging regions and regionalism as a primary frame of reference in late eighteenth and early nineteenth-century culture. Gerard Lee McKeever is Lecturer in Modern Scottish Literature at the University of Edinburgh, UK. He is the author of Dialectics of Improvement: Scottish Romanticism, 1786–1831 (2020), the winner of the BARS First Book Prize 2021.